Exodyssey : visual development of an epic adventure by Steambot Studios. - Larroude, Sebastien, ....-; Doizon, Thierry, ....-; Ferrand, Nicolas, ....- (Culver City : Designstudio, 2009)
From Steambot Studios, the cutting edge team of digital artists and concept designers who are currently working on the hotly anticipated blockbuster Tron 2, comes Exodyssey, a stunning 'art of? book which acts as an introduction to an epic new sci-fi saga, set in a brilliantly realised future world. It's not a movie or a video game... yet!Mixing character and vehicle designs with fully painted 'production art?-style visuals of environments, from a polluted future Earth to the Moon, Mars, and beyond into deep space and the mysterious planet code-named 'Samhuinn', the book outlines the voyage of Harry, a highly gifted engineer, and his dysfunctional team of followers, as they escape an evil empire and make first contact with extra-terrestrial life.